Chemistry of the Mediterranean Diet - Delgado, Amélia Martins; Vaz Almeida, Maria Daniel; Parisi, Salvatore (Springer International Publishing : Imprint: Springer, 2017)
Have you ever wondered what makes the Mediterranean diet so healthy? Do you enjoy olives, tomatoes, Chouriço and Mozzarella, basil, rosemary and oregano, grapes, figs, and dates; and would you like to learn more about the substances they contain? Then this book is for you! The Mediterranean diet, designated as an 'Intangible Cultural Heritage of Humanity', has a reputation of being particularly beneficial to your health and for reducing the risk of diseases like cardiovascular disorders. Read this book to find out which chemical compounds contribute to these health benefits. Typical ingredients of the Mediterranean diet include olive oils, fresh and dried vegetables and fruits, cereals, moderate amounts of fish, dairy and meat, and various condiments and spices, typically accompanied by wine and infusions. The book will introduce you to the most typical ingredients, providing information about their use in Mediterranean cuisine and explaining more about the healthy substances they contain - from their chemistry to their occurrence in the foods and the resulting intake. Summarizing important facts and data from available scientific literature, this book even gives recommendations for guidelines to a healthy diet - guidelines that are becoming more and more important. In recent years, it has been observed that nutritional habits in the geographical area have started to deviate further and further away from the typical Mediterranean nutritional pattern, representing an alarming trend that this book also critically addresses, since the WHO has reported increases in obesity and malnutrition in the Mediterranean area. Illustrations of important chemical compound structures, as well as appetizing photos of select ingredients for Mediterranean dishes, accompany the text.